(untitled) (Marketing Journal, 2025)
In the article, the issue of financing the innovative activities of business entities is examined, and this problem has become increasingly relevant under the conditions of ensuring the innovative development of the national economy. To address this issue, three main research methods were applied: scientific -theoretical, theoretical -practical, and economic -statistical analysis. The results of the study substantiate the significant role of the state in financing the innovative activities of business entities . Through scientific -theoretical investigation, analysis of the current situation, and the development of scientific and practical recommendations, the author has made a meaningful scientific and practical contribution to addressing the research problem.